Review efek ekstrak tanaman berbeda sebagai anti-toxocara - Gosha G. Parugrug; Desy Cahya Widianingrum; Listya Purnamasari; Himmatul Khasanah; Joseph Flores dela Cruz (Jurnal Ilmu Ternak, 2022)
Toxocara canis and Toxocara cati are important zoonotic parasites of dogs and cats. The increasing use of medicinal plants as anti-parasitic agents are attributed to its advantages like less side effects, with lower risk of anthelmintic resistance, and as cheaper alternatives. Although there are still no reports of anthelmintic resistance in Toxocara spp, the tendency of it happening should always be anticipated. This review summarized the in vitro and in vivo studies of the anti-Toxocara activity of plants, to enumerate the different plant extracts and the isolated active compounds in relation to their activity. In vitro studies investigated were primarily done in Toxocara larvae, mostly second-stage larvae, while in vivo studies were performed in animals mainly to assess the effect of the plant extracts on larval migratory behavior. Among the all plants described in this review, family Asteraceae was the most studied for their anthelmintic activity against toxocara species. The isolated active compounds with promising results were pyrethrin, kaurenes, palasonin, certain piperamides and curcuminoids, asarone, ascaridole, quercetin, thymohydroquinone (TQ), and secondary metabolites like flavonoids, alkaloids, tannins, saponins, and glycosides. However, The mechanism of action of each active ingredient of the plant as an anti-toxocara requires further research.